Autoimmune biliary diseases: primary biliary cholangitis and primary sclerosing cholangitis - Sarcognato, Samantha; Sacchi, Diana; Grillo, Federica; Cazzagon, Nora; Fabris, Luca; Cadamuro, Massimiliano; Cataldo, Ivana; Covelli, Claudia; Mangia, Alessandra; Guido, Maria (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Autoimmune cholestatic liver diseases are rare hepato-biliary disorders characterized by a progressive, inflammatory destruction of bile ducts. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are the main autoimmune cholestatic liver diseases. Both may evolve into secondary biliary cirrhosis and its complications. Therapeutic options are limited and liver transplantation remains the only definitive treatment for PBC and PSC. Most PBC and PSC patients have a typical presentation, which does not require liver biopsy. However, in routine clinical practice, important variants or specific subgroups that benefit from liver biopsy for proper management may be observed. Herein, we provide a general overview of clinical and pathological characteristic of PBC and PSC, highlighting the most important features for routine diagnostic practice.